Morphological and molecular characterization of Hemicycliophora subbotini n. sp. (Tylenchida: Hemicycliophoridae) from China - Maria, Munawar; Cai, Ruihang; Qu, Nan; Castillo, Pablo; Zheng, Jingwu (Zootaxa, 2018)
Sheath nematodes of the genus Hemicycliophora are migratory root-ectoparasites of many crops, but the damage is documented for only a few species. Hemicycliophora subbotini n. sp., isolated in Hangzhou, Zhejiang, China, from the rhizosphere of camphor tree (Cinnamomum camphora (L.) Presl), is described and characterized morphologically and molecularly with important morphological details elucidated by SEM studies. The new species can be characterized by the conoid lip region, with bulging oral disc protruding beyond the first annulus in some specimens. Oral disc narrow ovate, amphidial apertures covered by lateral plates, lying in the same plane as oral disc when observed en face. Stylet 118 (108–125) μm long and flexible, stylet knobs concave shaped having a slight cavity. The excretory pore is located 1–2 annuli posterior to the base of pharyngeal bulb. Vulval lips slightly modified with small vulval sleeve, spermatheca rounded to oblong. Anus located 18 (15–22) annuli posterior to vulva. Tail elongated, with conoid or slightly offset spike having a narrowly rounded terminus. The study provides the first description of a new Hemicycliophora species from China. Phylogenetic analyses based on D2–D3 expansion segments of the 28S and ITS fragments revealed the new species forming a separate clade from other Hemicycliophora species which supported the status as a new species of this genus.